(3ehShYI cfhR GdeYQaIs - (3TQHd, ehQjS CSYOs; (3GdaJj, efjQs; (3jYbhH, Eejd HOjYs ((3Lhfjg, dHfGf (B:s (3OGQ fXjQ YHhO,s, 2001)
(3jJfGhd ehVhY GdYdhe (B: (3GdcjejGA hGdajRjGA hGdCMjGA hGdHjFI hGdJdhK(B.s
(3JJchf GdehShYI ef (B16 (3eLdO efbSejf Edi ehGVjY cd eLdOjf ehVhY(B.s
(3GdecJHI jJhGaQ HgG (B: (3eL(B. 13(3, (B14.s
Keywords: (3OhGFQ GdeYGQa GdYQHjIs